Analysis of Determinants of Inflation in ASEAN: Evidence from Exchange Rate, GDP, Interest Rate, Broad Money, and Trade (2012-2024) - Difa Kusuma Dewa; Eni Setyowati (Jurnal Economic Resource, 2026)
This study's goal is to investigate how exchange rates, GDP growth, interest rates, broad money, and trade openness affect inflation in six ASEAN nations between 2012 and 2024. The sample consists of Indonesia, Malaysia, Vietnam, Brunei Darussalam, Timor-Leste, and the Thailand. The Consumer Price Index, or CPI, is employed in the computation of inflation. The World Bank, Asian Development Bank, and International Monetary Fund provided the panel data utilized in this investigation, which is secondary data. The outcomes of the Fixed Effect Model robust standard error estimate demonstrates that the exchange rate has a substantial and detrimental impact on inflation with a probability value of 0.015. Likewise, GDP and Interest rate. Meanwhile, broad money has a substantial and favorable impact on inflation. However, Trade has no discernible impact on inflation with a probability of 0.551. By using the Fixed Effect Model, a coefficient of determination of 80.25% of changes in inflation can be clarified by the variables used in the model, such as the exchange rate, GDP, interest rate, broad money, and trade. The remaining 19.75% is explained by factors that are not part of the model. This research shows that monetary and macroeconomic factors are crucial in influencing inflation in ASEAN countries. Therefore, maintaining exchange rate stability, controlling the broad money, and appropriately regulating interest rate policies are crucial to maintaining price stability in the ASEAN region.